2020
DOI: 10.1093/abm/kaaa018
|View full text |Cite
|
Sign up to set email alerts
|

Precision Health: The Role of the Social and Behavioral Sciences in Advancing the Vision

Abstract: Background In 2015, Collins and Varmus articulated a vision for precision medicine emphasizing molecular characterization of illness to identify actionable biomarkers to support individualized treatment. Researchers have argued for a broader conceptualization, precision health. Precision health is an ambitious conceptualization of health, which includes dynamic linkages between research and practice as well as medicine, population health, and public health. The goal is a unified approach to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
132
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(133 citation statements)
references
References 149 publications
(139 reference statements)
0
132
0
1
Order By: Relevance
“…Our study revealed similar results to previous studies that impulsivity is not a unitary construct but is rather composed of qualitatively different constructs, which may or may not have some overlap [ 22 ]. Moreover, the complex relationship between impulsive behaviors and health outcomes within each individual might require an n-of-1 approach to prediction and control of impulsive behaviors [ 37 , 88 , 89 ]. New mHealth methods such as the DMT using multimodal assessment strategies that take trait and state impulsivity into account with contextual variables are needed to further our understanding of how to predict impulsive behavior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study revealed similar results to previous studies that impulsivity is not a unitary construct but is rather composed of qualitatively different constructs, which may or may not have some overlap [ 22 ]. Moreover, the complex relationship between impulsive behaviors and health outcomes within each individual might require an n-of-1 approach to prediction and control of impulsive behaviors [ 37 , 88 , 89 ]. New mHealth methods such as the DMT using multimodal assessment strategies that take trait and state impulsivity into account with contextual variables are needed to further our understanding of how to predict impulsive behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies should account for contextual factors such as setting, mood, and intentionality to further disentangle the relationship between trait and state impulsivity, and the different dimensions measured by these tools. Contextual factors can also be used to design more precise behavior change and digital health interventions with mobile technology [ 88 , 90 - 93 ].…”
Section: Discussionmentioning
confidence: 99%
“…Precision medicine [ 1 ] and precision health [ 2 ] (i.e., diagnostics and treatment strategies that take individual variability into account) have been greatly expanded in the past years through a variety of methods and computational techniques, such as genome sequencing, big data, and wearable technology. These initiatives aim to progressively move beyond approaches focused on average patient responses toward ones that are individualized, contextualized, and timely [ 2 ]. In this article, we aim to provide an overview of key methods and approaches that can help facilitate the transition to precision initiatives in the health behavior change domain.…”
Section: Accounting For the Inherent Complexity Of Health Behavior Chmentioning
confidence: 99%
“…The amounting evidence that health behaviors are complex suggests that adaptive and continuous “tuning” interventions are necessary for better supporting healthy behavioral choices over time and across contexts, similar to what a clinician or health coach would do in their practice [ 2 , 69 ]. The idea that tailored interventions are more likely to engender change at the individual level (as opposed to static or generic interventions) is not new; tailoring refers to a category of interventions which aim to “reach one specific individual, based on specific characteristics of that person that have been measured in a formal assessment” [ 70 ].…”
Section: Accounting For the Inherent Complexity Of Health Behavior Chmentioning
confidence: 99%
“…However, in personalized, for example, just-in-time adaptive interventions, where participants are prompted with messages suited to them, based on data (e.g. (35), expectations of enactment are likely to be higher, and monitoring whether participants enact the BCTs tailored precisely to them (36) should become all the more important. These interventions may also offer exciting opportunities to investigate what factors improve uptake of offered BCTs, and inter-individual variation therein.…”
Section: Improving Promotion Of Enactment Of Bctsmentioning
confidence: 99%